Development and Validation of a Life Satisfaction Instrument in Human Resource Practitioners of Thailand - Khahan Na-Nan; Supakit Wongwiwatthananukit (Journal of Open Innovation: Technology, Market and Complexity, 2020)
The purpose of this paper was to develop and validate an instrument to measure life satisfaction (LS). Eighteen items were selected to assess the LS questionnaire developed from concepts and theory. The questionnaire was applied as a cross-sectional study and data were collected as establishing factors to confirm and ascertain construct validity. Reliability was tested by measuring internal consistency. Relationships with family and other people, personal life, life and society, and working life and self-development factors were identified. Findings confirmed the constructs between theoretical concepts and empirical evidence. The validity of this LS questionnaire will facilitate future studies to test the boundaries of LS assessment in the context of Human resource (HR) practitioners. This instrument can support and assist researchers to develop a comprehensive and intuitive understanding of LS and promote further investigation of its potential in future studies.